Helminths in Invasive Raccoons (Procyon lotor) from Southwest Germany - Nico P. Reinhardt; Marion Wassermann; Jessica Härle; Thomas Romig; Lina Kurzrock; Janosch Arnold; Ernst Großmann; Ute Mackenstedt; Reinhard K. Straubinger (Pathogens, 2023)
As hosts of numerous zoonotic pathogens, the role of raccoons needs to be considered in the One Health context. Raccoons progressively expand their range as invasive alien species in Europe. This study aimed to investigate the intestinal helminth fauna of raccoons in Baden-Wuerttemberg, Germany, as no such screening had ever been conducted there. In total, we obtained 102 animals from hunters in 2019 and 2020. Intestinal helminths were retrieved using the SSCT (segmented sedimentation and counting technique) and identified morphologically and by PCR-based Sanger sequencing. Fecal samples were assessed using the ELISA PetChekTM IP assay (IDEXX, Germany) and flotation technique. The artificial digestion method was employed for analyzing muscle tissue. We detected species of four nematode genera (Baylisascaris procyonis, Toxocara canis, Capillaria spp., and Trichuris spp.), three cestode genera (Atriotaenia cf. incisa/procyonis, Taenia martis, and Mesocestoides spp.), and three trematode genera (Isthmiophora hortensis/melis, Plagiorchis muris, and Brachylaima spp.). Echinococcus spp. and Trichinella spp. were not found. The invasive behavior and synanthropic habits of raccoons may increase the infection risk with these helminths in wildlife, domestic and zoo animals, and humans by serving as a connecting link. Therefore, it is crucial to initiate additional studies assessing these risks.